REGIONAL THEORETICAL AND PRACTICAL CONFERENCE «TIMELY PEDIATRIC PROBLEMS» - A.A. Автор ("Paediatrician" Publishers LLC, 2011)
(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 176-177.)